Economic hardship and policy preferences in the eurozone periphery: Evidence from spain - Fernandez-Albertos, J; Kuo, A (SAGE Publications, 2016)
What is the impact of economic suffering on support for euro membership and austerity policies in the Eurozone periphery? This article uses original public opinion and firm surveys conducted in Spain in the midst of the great recession to describe the structure of preferences toward the euro as a common currency and austerity policies, focusing on the specific impact of crisis exposure. We find that in spite of the depth and the duration of the economic crisis, support for Spain’s membership in the Eurozone is strong. However, while economic suffering divides the electorate on support for the euro and austerity, it does not do so for firms. Surprisingly, individuals who have suffered due to the crisis in terms of higher income loss are more skeptical of tax and spend programs but are more critical of the euro. Moreover, individuals who are skeptical of the euro and austerity are demographically distinct groups of people. One implication of our joint individual and firm-level findings is that a coalition to seriously challenge the status quo policy coalition remains difficult.